Bioenergy and agriculture: Promises and challenges: Bioenergy in Europe: Experiences and prospects - Henniges, Oliver; Zeddies, Jürgen (International Food Policy Research Institute, 2006)
Although Europe is a relatively small producer of ethanol (2.6 percent of world production in 2005), it produces a sizable share of the world’s biodiesel (88 percent of world production in 2005). Production started in the early 1990s (well after Brazil and the United States; see Figure 1), when revisions to the Common Agricultural Policy (CAP) first allowed farmers to grow nonfood crops for income on set-aside land. Germany began to produce biodiesel from rapeseed, while France undertook production of bioethanol from sugar beet and wheat. Today, Germany is the world’s largest biodiesel producer, with a total existing capacity of more than 2 million metric tons per year, representing more than 5 percent of domestic diesel demand.